To what extent do Gestalt grouping principles influence tactile perception? - Gallace, A; Spence, C (2011)
Since their formulation by the Gestalt movement more than a century ago, the principles of perceptual grouping have primarily been investigated in the visual modality and, to a lesser extent, in the auditory modality. The present review addresses the question of whether the same grouping principles also affect the perception of tactile stimuli. Although, to date, only a few studies have explicitly investigated the existence of Gestalt grouping principles in the tactile modality, we argue that many more studies have indirectly provided evidence relevant to this topic. Reviewing this body of research, we argue that similar principles to those reported previously in visual and auditory studies also govern the perceptual grouping of tactile stimuli. In particular, we highlight evidence showing that the principles of proximity, similarity, common fate, good continuation, and closure affect tactile perception in both unimodal and crossmodal settings. We also highlight that the grouping of tactile stimuli is often affected by visual and auditory information that happen to be presented simultaneously. Finally, we discuss the theoretical and applied benefits that might pertain to the further study of Gestalt principles operating in both unisensory and multisensory tactile perception.